Pro Google cloud automation : with Google Cloud Deployment Manager, Spinnaker, Tekton, and Jenkins - Sabharwal, Navin; Pandey, Piyush (Apress, 2021)
Discover the methodologies and best practices for getting started with Google cloud automation services including Google Cloud Deployment Manager, Spinnaker, Tekton, and Jenkins to automate deployment of cloud infrastructure and applications. The book begins with an introduction to Google cloud services and takes you through the various platforms available to do automation on the GCP platform. You will do hands-on exercises and see best practices for using Google Cloud Deployment Manager, Spinnaker, Tekton, and Jenkins. You'll cover the automation aspects of the Google Cloud Platform holistically using native and upcoming open source technologies. The authors cover the entire spectrum of automation from cloud infrastructure to application deployment and tie everything together in a release pipeline using Jenkins. Pro Google Cloud Automation provides in-depth guidance on automation and deployment of microservices-based applications running on the Kubernetes platform. It provides sample code and best practice guidance for developers and architects for their automation projects on the Google Cloud Platform. This book is a good starting point for developers, architects, and administrators who want to learn about Google cloud automation. You will: Gain the fundamentals of Google's automation-enabling services See an architecture overview for Google Cloud Deployment Manager, Spinnaker, Tekton, and Jenkins Implement automation for infrastructure and application use cases Automate microservices-based applications running on GKE Enable Google Cloud Deployment Manager, Spinnaker, Tekton, and Jenkins.